THE EVALUATION OF KINDERGARTEN’S TAHFIZH QURAN PROGRAMME IN BANDA ACEH, INDONESIA USING CIPP MODEL - Ningsih, Yunita; Che Mustafa, Mazlina; Hasyim, Ibrahim (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
This study aims to evaluate the effectiveness of the implementation the Teaching Tahfizh Quran programme for kindergarten children using the Stufflebeam’s Context, Input, Process and Product (CIPP) Evaluation Model. This qualitative approach study applied an explanatory design analysis of CIPP model in evaluating the two Islamic kindergartens in Aceh, Indonesia. Those kindergartens were selected as they have an intensive Tahfizh Quran Programme for early age children. Data were collected through interviews, observation, and documentation then the data were analysed, interpreted descriptively. A semi-structured interview form and an observation form were used as data collection tools. Data were deployed to two teachers, two principals; two parents. Hence, two groups were observed during the teaching and learning process of Tahfizh Quran Programme. Ten children of the group were selected as the samples using a saturated sampling technique. The thematic analysis was selected, the findings for the context revealed that the physical infrastructure of kindergarten education institutions should be improved. Regarding the input dimension, it was found that the tahfizh curriculum has been well prepared, family factor and the individual differences of the children have been collaborated. Regarding the process dimension, it has emerged that studies the least done were the implementation of qualified home practices, assessment studies and the addition or removal of learning centers as needed. In the product dimension, the kindergarten principals and teachers have committed to develop a good communication with parents and communities either institutionally or non-institutionally. The results of the research supported theories dealing with tahfizh learning programme both theoretically and practically. Practically, children cognitive intelligence has been the newly positive achievement of being a huffazh in early age, memorizing Quran in kindergarten also improved the children ability in memorizing other knowledge, results of this research have given benefits to the tahfizh teachers, especially in guiding students to memorize Quran in an effective way. It encouraged students’ awareness of memorizing Quran on Islamic Education development in kindergartens in Aceh province, Indonesia.